2020
DOI: 10.32693/bomg.35.2.2020.690
|View full text |Cite
|
Sign up to set email alerts
|

Estuary Changes of Cipunagara and Cimanuk River Using Landsat Imagery Spatial Analysis

Abstract: The north coastal Java located in the West Java, especially in Cirebon, Indramayu, and Subang, occurs loss and forming new land by abrasion and accretion processes. Observation using satellite imagery can be used as an initial stage to determine the distribution of abrasion and accretion around the north coastal area. Observation of land changes was assigned using Landsat imagery from 1978 to 2020. The result shows that inland change was controlled by abrasion and accretion. It is occurred in Indramayu and Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Therefore, this study focused on identifying the potential of hydropower as a renewable energy in Indonesia using geospatial and empirical approaches. The process involved highlighting several track records in the country, specifically in the Cipunegara watershed, such as the study conducted to determine the estuary changes in Cipunagara and Cimanuk Rivers using landsat imagery spatial analysis (Nur et al, 2020), and characterization of hydrocarbon reservoirs in Ozara Field, North West Java Basin using acoustic impedance inversion analysis (Zacky, 2020).…”
Section: Article Infomentioning
confidence: 99%
“…Therefore, this study focused on identifying the potential of hydropower as a renewable energy in Indonesia using geospatial and empirical approaches. The process involved highlighting several track records in the country, specifically in the Cipunegara watershed, such as the study conducted to determine the estuary changes in Cipunagara and Cimanuk Rivers using landsat imagery spatial analysis (Nur et al, 2020), and characterization of hydrocarbon reservoirs in Ozara Field, North West Java Basin using acoustic impedance inversion analysis (Zacky, 2020).…”
Section: Article Infomentioning
confidence: 99%
“…In total, the annual rainfall in those villages was 5,297 mm in 2018 (BPS Kabupaten Subang 2019). In the context of watershed management, earlier studies have demonstrated that the Cipunagara watershed has experienced landcover changes leading to soil erosion, water pollution, sediment transport, and water arrangement disturbances (Fitriyana et al 2020;Juwana and Nugroho 2020;Nur et al 2020). For instance, Fitriyana et al (2020) elucidated that the highest sediment transported through the river in the Cipunagara watershed was more than 1 million tons.…”
Section: Study Sitementioning
confidence: 99%